APLIKASI PENCARIAN ASISTEN RUMAH TANGGA “ASISTENKU” BERBASIS ANDROID - Muhammad Fahrurrozy Alwi; Ardiansyah Ardiansyah; Anie Rose Irawati (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
The meaning of assistants is a person whose duty as to assist other assistants and maid is specific assistant for housework. The maid is a job that people choose a lot because of economic factors and poor education. Families who are doing a lot of activities outside the home certainly need assistants to take care of the needs of the housework. A conventional way of finding assistants is to go to the homes assisted foundations or ask other people. In this study, were developed to ease in finding assistants. This application helps users to assistants search for example maid, baby sitters, drivers, and security by displaying the availability of assistants and tariffs offered. The application has been tested for functional and non-functional using Likert scale. Based on functional testing known that the application has met the required function and based on non-functional testing it is known that the respondents' assessment of the application is an 92% points which is very good.